2020
DOI: 10.1186/s12864-020-07084-x
|View full text |Cite|
|
Sign up to set email alerts
|

Fine-scale population structure and evidence for local adaptation in Australian giant black tiger shrimp (Penaeus monodon) using SNP analysis

Abstract: Background Restrictions to gene flow, genetic drift, and divergent selection associated with different environments are significant drivers of genetic differentiation. The black tiger shrimp (Penaeus monodon), is widely distributed throughout the Indian and Pacific Oceans including along the western, northern and eastern coastline of Australia, where it is an important aquaculture and fishery species. Understanding the genetic structure and the influence of environmental factors leading to adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 104 publications
(152 reference statements)
2
15
1
Order By: Relevance
“…The main difference in genetic structure was that the Western Australian (WA) population was a discrete cluster (neutral SNPs) versus part of the Northern Australia and Philippines (NAP) cluster (outlier SNPs). Recently, Vu et al (2020) demonstrated that P. monodon from a Western Australian population was genetically divergent from multiple Eastern and Northern Australia populations (i.e., discrete cluster) based on outlier loci determined using EnA analyses ( n = 89 SNPs). We believe that the difference between the present study and Vu et al (2020) is most likely due to outlier determination being based on PD versus EnA analyses ( n = 663 vs. 89), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The main difference in genetic structure was that the Western Australian (WA) population was a discrete cluster (neutral SNPs) versus part of the Northern Australia and Philippines (NAP) cluster (outlier SNPs). Recently, Vu et al (2020) demonstrated that P. monodon from a Western Australian population was genetically divergent from multiple Eastern and Northern Australia populations (i.e., discrete cluster) based on outlier loci determined using EnA analyses ( n = 89 SNPs). We believe that the difference between the present study and Vu et al (2020) is most likely due to outlier determination being based on PD versus EnA analyses ( n = 663 vs. 89), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Vu et al (2020) demonstrated that P. monodon from a Western Australian population was genetically divergent from multiple Eastern and Northern Australia populations (i.e., discrete cluster) based on outlier loci determined using EnA analyses ( n = 89 SNPs). We believe that the difference between the present study and Vu et al (2020) is most likely due to outlier determination being based on PD versus EnA analyses ( n = 663 vs. 89), respectively. Other non-SNP studies also reported P. monodon from Western Australia as being genetically distinct from other Australian P. monodon populations ( Brooker et al 2000 ; Benzie et al 2002 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After publication of this article [ 1 ], it is noticed the article contained an error: Fig. 3 erroneously contained panel B as a copy of panel A instead of the correct panel B illustration.…”
mentioning
confidence: 99%